2009
DOI: 10.1128/jcm.00750-09
|View full text |Cite
|
Sign up to set email alerts
|

Serological Immunoassay for Detection of Hepatitis E Virus on the Basis of Genotype 3 Open Reading Frame 2 Recombinant Proteins Produced in Trichoplusia ni Larvae

Abstract: Hepatitis E virus (HEV) is a major cause of acute hepatitis in humans, and strains of genotypes 1 and 2 are endemic in many regions with suboptimal sanitary conditions. In many industrialized countries, HEV strains of genotype 3 are highly endemic in swine, and an increased number of autochthonous infections with HEV genotype 3 strains have been reported lately. Serological studies of HEV infection are often conducted with commercial assays based on peptides and recombinant proteins of HEV genotype 1 and 2 str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 33 publications
(48 reference statements)
2
23
0
2
Order By: Relevance
“…We have shown that insect-derived recombinant proteins produced in insect larvae used as living biofactories, even in its raw form, are useful for diagnosis [25], [26], [27], [28], [29], [30], [31], including that of leishmaniasis [32], [33], and vaccination [34], [35], [36], [37].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that insect-derived recombinant proteins produced in insect larvae used as living biofactories, even in its raw form, are useful for diagnosis [25], [26], [27], [28], [29], [30], [31], including that of leishmaniasis [32], [33], and vaccination [34], [35], [36], [37].…”
Section: Introductionmentioning
confidence: 99%
“…(29). Most of these EIAs employ for antibody capture antigens that are derived from HEV genotypes 1 and 2 and so may not be sufficiently sensitive to detect heterotypic antibodies generated in human and animal hosts infected by genotype 3 (19,24,45,48) or genotype 4 (2,23,62). Moreover, some indirect EIAs tend to generate false-positive reactivities (52,65) and therefore require, in order to validate the specificity of their reactivities, the extra steps of neutralization, immunoblotting, or prior production of genus-specific positive controls (1,12,35,45).…”
Section: Dasa Reactivity In Diverse Animal Groupsmentioning
confidence: 99%
“…Moreover, in most assays, the antigens used for antibody capture are derived from HEV genotype 1 or genotypes 1 and 2. Because the HEV genotypes thus far identified to infect animals belong instead to genotype 3, genotype 4, and the newer putative genotypes, the possibility that low antibody detection rates reflect weak binding of antibody to heterotypic antigens rather than true antibody absence (2,19,24,44,45,48,62) cannot be excluded.…”
mentioning
confidence: 99%
“…However, most of these studies have been conducted using HEV ELISA that are based on genotype 1 or 2 peptides and are designed for humans, but not for swine (Pintó and Saiz 2007). Actually, these assays sometimes failed to detect specific antibodies in sera from individuals with proven HEV gt3 infections Jiménez de Oya et al 2009b). …”
mentioning
confidence: 98%